PENGARUH MANAJEMEN BAKAT DALAM MEMPERTAHANKAN KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - Pramarta, Kadek Dimas; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen; Vol 7 No 12 (2018), 2018)
The purpose of this study was to examine the influence of talent management in maintaining employees with organizational commitment as a moderating variable in employees of PT. Rara Lestari Global. In this study used the census method (total sampling) in determining the sample of 55 respondents, through moderation analysis techniques (MRA). Based on the results of the analysis shows that all hypotheses can be accepted that is 1) Talent management has a positive and significant influence in retaining employees. 2) Organizational commitment has a positive and significant influence in retaining employees. 3) Organizational commitment is able to moderate the positive relationship of talent management in retaining employees. Suggestions recommended companies should conduct training, socialization, cultivate talent so that workers are able to work well with a good talent for corporate purposes. Unstructured job base on employees make employees feel burdened this should be the special attention of the management so that the responsibilities and obligations of employees in accordance with what is done so that employees stay at PT. Rara Lestari Global Bali.